Studi Kelayakan Pembangunan Tribun Penonton Di Sirkuit Kebun Buah Tlogo Tuntang Kabupaten Semarangg - Melinda Sibu; Henanda Dian Pramana; Maria Christy Karatahi; Jerry A Tjuluku; Roos Kities Andadari (RESEARCH FAIR UNISRI, 2024)
This study evaluates the technical, market, and financial feasibility of building an audience stand at the Tlogo fruit garden circuit, a tourism attraction that combines agricultural and automotive aspects. The research method is qualitative descriptive, using data collection techniques such as observation, interviews, and documentation. The results show that the audience stand can enhance the viewing experience of visitors who watch motorcycle or car races, as well as increase the potential of visitors and revenue. The audience stand construction project is also profitable, with a payback period of 1.52 years, a positive net present value of Rp 314.956.392, and an interest rate return of 67.89 percent.